Paleopathological interpretation of trepanima pallidum in 18th century crypt assemblages from Christ Church, St. Luke & St. George, London - Clark, Ryan N. (My University, 2010)
This paper covers both the osteological and paleopathological interpretation of three crypt assemblages from Christ Church, St Luke and St George London. Each of the three sites had varying numbers of individuals analyzed. St George?s assemblage contained 111 individuals; St Luke?s contained 896 while Christ Church?s was made up of 968 individuals, statistical analysis was taken to understand the demographic and spatial distribution of Trepanima Pallidum. Rates at St George were higher than the remaining other two sites. This was due to the wealth of the parish and its proximity to Covent Garden. St Luke?s rates were comparable if lower, due to their proximity to The Rookery and their economic status. Lastly, Christ Church?s rates were the lowest, due to their distance from the city center and the strength of their family units.
Keywords: Antiquities.; Archaeology and history.; Excavations (Archaeology) -- History.